Loss of DUSP3 activity radiosensitizes human tumor cell lines via attenuation of DNA repair pathways - Torres, Thompson E.P.; Russo, Lilian C.; Santos, Alexsandro; Marques, Gabriela R.; Magalhaes, Yuli T.; Tabassum, Sartaj; Forti, Fabio L. (Biochimica et biophysica acta. General subjects, 2017)
Radiotherapy causes the regression of many human tumors by increasing DNA damage, and the novel molecular mechanisms underlying the genomic instability leading to cancer progression and metastasis must be elucidated. Atypical dual-specificity phosphatase 3 (DUSP3) has been shown to down-regulate mitogen-activated protein kinases (MAPKs) to control the proliferation and apoptosis of human cancer cells. We have recently identified novel molecular targets of DUSP3 that function in DNA damage response and repair; however, whether DUSP3 affects these processes remains unknown. Tumor cell lines in which DUSP3 activity was suppressed by pharmacological inhibitors or a targeted siRNA were exposed to gamma radiation, and proliferation, survival, DNA strand breaks and recombination repair pathways were sequentially analyzed. The combination of reduced DUSP3 activity and gamma irradiation resulted in decreased cellular proliferation and survival and increased cellular senescence compared with the effects of radiation exposure alone. Gamma radiation-induced DNA damage was increased by the loss of DUSP3 activity and correlated with increased levels of phospho-H2AX protein and numbers of ionizing radiation-induced γ-H2AX foci, which were reflected in diminished efficiencies of homologous recombination (HR) and non-homologous end-joining (NHEJ) repair. Similar results were obtained in ATM-deficient cells, in which reduced DUSP3 activity increased radiosensitivity, independent of increased MAPK phosphorylation. The loss of DUSP3 activity markedly increases gamma radiation-induced DNA strand breaks, suggesting a potential novel role for DUSP3 in DNA repair. The radioresistance of tumor cells is effectively reduced by a combination of approaches through the inhibition of DUSPs. [Display omitted] •DUSP3 inhibition or knockdown increases DNA damage caused by gamma radiation.•DUSP3 inhibition or knockdown reduces DNA repair in tumor cells.•DUSP3 inhibition or knockdown reduces the proliferation and survival of tumor cells.•DUSP3 inhibition increases the cellular senescence of tumor cells.•The effects of the loss of DUSP3 activity are more apparent in ATM-deficient cells.